The Influence of Educational Background and Learning Interest on Academic Performance in Higher Education - Rizqiyah Ning Rahayu (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2025)
This study aims to examine the influence of educational background and learning interest on students' academic achievement in higher education. Student interest is a strong predictor of academic success, while educational background contributes to academic readiness, although their impact varies across contexts. However, the combined effects of these factors remain underexplored, particularly in non-Western educational settings. Using a quantitative correlational design, this study collected data through questionnaires and conducted statistical analyses using Pearson correlation and multiple regression. The study sample consisted of students enrolled in the Intensive Arabic Language Program at UIN Sunan Ampel Surabaya. The findings reveal a moderate correlation between learning interest, educational background, and academic performance, with an overall R-value of 0.541. Regression results show that learning interest significantly predicts academic achievement (β = 0.541, p < .001), indicating that higher interest strongly enhances performance. Conversely, educational background demonstrates no significant effect (p = .821), suggesting limited predictive value in this context. The model explains 27.6% of the variance, indicating that other factors also shape student outcomes. This study contributes to understanding how motivational and contextual variables interact in language learning and recommends that educators prioritize strategies that strengthen student engagement.